INVESTOR BEHAVIOR MODEL TOWARD TRADING ROBOTS: AN INITIAL TRUST AND SOCIAL INFLUENCE APPROACH - Gunawan, Revalina; Wiryakusuma, I Gusti Bagus Yosia (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze investor behavior in adopting trading robots by highlighting the role of initial trust and social influence on behavioral intention. The urgency of this research lies in the rapid growth of robo-advisor services in Indonesia, which still faces challenges such as low financial literacy and weak initial investor trust, while investment decisions are often influenced by social opinions. The study population includes individuals aged 17–59 years who use trading robots, with a total of 167 respondents obtained through an online questionnaire. Data analysis was conducted using a quantitative method with Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results indicate that social influence has a significant effect on both initial trust and behavioral intention. In addition, initial trust positively influences behavioral intention and serves as a mediator in the relationship between social influence and behavioral intention. Meanwhile, the age variable does not moderate the relationship between initial trust and behavioral intention. These findings emphasize that initial trust is a key factor in shaping investors’ intentions to adopt trading robots. Therefore, service development strategies should focus on strengthening trust from the early stages of user interaction and enhancing social influence through education, testimonials, and community engagement.